Korelasi Layanan Pemulihan dengan Citra Rumah Sakit di Ruang Rawat Inap RSUD Lamaddukkelleng Sengkang - Andi Mikhrunnisai; Anugerah Yanuar Azis; A. Nur Azizah; Nur Fadilah Fitrah (Journal Research of Health Administration and Public Health (JRHAPH), 2025)
In modern hospital management, the relationship between service recovery and hospital image is a strategically crucial aspect for maintaining institutional credibility. RSUD Lamaddukkelleng Sengkang faces challenges related to the effectiveness of communication and inconsistent complaint handling, which potentially influence patients’ perceptions. This study aimed to examine the correlation between service recovery and hospital image in the inpatient wards of RSUD Lamaddukkelleng Sengkang. A cross-sectional approach was employed, using proportional stratified random sampling with 100 respondents drawn from a total patient population of 14,204. Inclusion criteria included patients who had undergone a minimum of 2 × 24 hours of inpatient care and were in a conscious state. Data were collected through questionnaires and analyzed using the Chi-Square test with SPSS version 16. The results indicated that the majority of respondents rated service recovery as adequate (62.0%) and hospital image as positive (72.0%). Bivariate analysis revealed a significant relationship between service recovery and hospital image. Most respondents (56.0%) who rated service recovery as adequate also provided a positive assessment of the hospital image. These findings confirm that the quality of service recovery plays a critical role in shaping the institution’s reputation. Effective service recovery not only addresses complaints but also rebuilds patients’ trust and loyalty. Strategies such as improving human resource competencies, developing integrated management information systems for rapid response, and maintaining the quality of the hospital’s physical environment are necessary to sustainably strengthen the hospital’s positive image.